2013
DOI: 10.1093/bja/aes468
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of goal-directed haemodynamic treatment in patients with proximal femoral fracture

Abstract: The magnitude of risk reduction of postoperative complications is clinically relevant, but the trial was underpowered and the null hypothesis cannot be rejected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 26 publications
(20 reference statements)
7
69
1
1
Order By: Relevance
“…The recognition and management of hypovolaemia in this population is challenging despite improvements in perioperative care. Bartha et al [6], in a recently reported trial of goaldirected therapy in hip fracture, had a response rate to fluid challenge of 37/142 (26%), which is similar to Canty et al's findings. Interestingly, Bartha and colleagues did not demonstrate the marked difference in mortality that Canty et al found.…”
Section: Kaufmansupporting
confidence: 78%
“…The recognition and management of hypovolaemia in this population is challenging despite improvements in perioperative care. Bartha et al [6], in a recently reported trial of goaldirected therapy in hip fracture, had a response rate to fluid challenge of 37/142 (26%), which is similar to Canty et al's findings. Interestingly, Bartha and colleagues did not demonstrate the marked difference in mortality that Canty et al found.…”
Section: Kaufmansupporting
confidence: 78%
“…The risk of hypovolaemia may be reduced by limitation of starvation times and with intravenous fluid administration before and during surgery. Intraoperative stroke volume guided fluid studies are currently underpowered to demonstrate statistically significant changes in development of AKI [46, 47] and echocardiography studies [48] suggest that around 25% of patients are still hypovolaemic immediately prior to theatre. Patients arriving in theatre with urinary evidence of ‘dehydration’ [49] also have a worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple single-center studies have shown that perioperative GDT may significantly improve outcome, particularly in patients undergoing abdominal surgery [3-5], but also in trauma [6,7] and orthopedic surgery [8]. All these studies were single-center studies which makes the meta-analysis that dealt with these highly divergent studies hard to interpret [9].…”
Section: Introductionmentioning
confidence: 99%